Younger patients with primary Sjögren's syndrome are more likely to have salivary IgG anti-muscarinic acetylcholine receptor type 3 antibodies. Issue 3 (March 2016) - Jayakanthan, K.; Ramya, J.; Mandal, Santosh; Sandhya, P.; Gowri, M.; Danda, Debashish
Abstract Acetylcholine type 3 receptor (M3R) is recognized as an autoantigen in primary Sjögren's syndrome (pSS). Assay of anti-M3R antibody levels in serum is fraught with low sensitivity for diagnosis of pSS. Salivary assay is more likely to improve the diagnostic accuracy. Patients with pSS classified either by the American European Consensus Group (AECG) or American college of Rheumatology (ACR) criteria, attending rheumatology clinic between October 2014 and July 2015 were included. Hospital staff and lupus patients constituted healthy and disease controls, respectively. Evaluation of pSS included clinical evaluation, laboratory tests, ESSDAI and ESSPRI scoring. Unstimulated saliva was collected by the spitting method. Salivary IgG antibody against M3R (anti-M3R) was quantified by indirect ELISA. In this study, 43 patients with pSS, 34 with lupus and 42 healthy controls were recruited. The frequency of anti-M3R antibody levels was 55.81, 17.64 and 7 % for pSS, lupus and healthy controls, respectively. Area under the Receiver Operator Characteristic was 0.7791 (95 % CI, , 0.67–0.87). Sensitivity and specificity of the assay for diagnosis of pSS were 44.19 and 88.16 %, respectively. Salivary anti-M3R IgG antibody positivity was associated with lower age, shorter disease duration and higher globulin levels in our cohort. Salivary anti-M3R IgG antibody assay has high specificity in pSS; younger patients and those with hyperglobulinemia more frequently tested positive for this antibody.